Total synthesis of selaginellin A. (31st August 2021) - Fujiwara, Kenshu; Itagaki, Takaya; Tokiwano, Tetsuo
Graphical abstract: Abstract: The total synthesis of selaginellin A, isolated from Selaginella tamariscina, was achieved through an eight-step process including a Diels-Alder reaction, formation of a quinone methide moiety and dehydrogenative aromatization. The NMR spectra collected for different samples of synthetic selaginellin A initially showed irregular peak shapes and variable chemical shifts for the signals of the phenol-substituted quinone methide moiety under neutral conditions. After detailed NMR analysis, it was found that the addition of a trace amount of trifluoroacetic acid accelerated the tautomerism of the phenol-substituted quinone methide moiety and improved the reproducibility of the chemical shifts of synthetic selaginellin A.